Micronutrients: Its role in intrauterine growth restriction - Rajbhandari, Swaraj; Dali, Sanu Maiya (Nepal Journal of Obstetrics and Gynaecology, 2009)
Objective: To find out the role of micronutrients in intrauterine growth restrictions. Methodology. Desktop review of articles from the year 1986 till 2005 March using key words, Micronutrients AND Intrauterine Growth Restriction. Results: 13.7 million infants are born annually with fetal growth restriction (IUGR) comprising 11% of all births in developing countries affecting up to 40% in some of developing countries varying from 14-38.8% for Nepal. Public health officials have recognized the urgent need for interventions aimed to prevent IUGR as this higher percent is likely due to protein calorie malnutrition, kwown to be the second leading cause of perinatal morbidity and mortality. The identification of IUGR is crucial because proper evaluation and management can result in a favourable outcome. Sixty five percent of IUGR are not identified until after delivery. More over, it is unrealistic issue to assume that extra nutrient taken for few months during pregnancy would replace the under nutrition that has been prevalent for over decades in terms of reproductive performance. Conclusion: Although it is frustrating that, most of the interventions aimed to prevent or treat impaired fetal growth have hardly shown any beneficial effect on short-term perinatal outcomes, long term benefit may be rewarding with significant impact. Hence provision of energy supplementation for two (or more, if they occur) consecutive pregnancies must be focused rather than during single pregnancy. Key words: micronutrients, intrauterine growth restriction, malnutrion. doi:10.3126/njog.v1i2.2407 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 77-82 Nov-Dec 2006